Awareness of Healthcare Providers About COVID-19 Vaccinations in Karbala City - Atta Ah. Mousa Al-Sarray; Rasha Haider Shareef (Journal of Techniques)
The process of creating a vaccination is more complex and challenging than that of creating medication. The immunization has developed over a period of 12 to 15 years. It would probably take months to design and manufacture a coronavirus vaccine, which is a significant hurdle. Despite promises from several groups that a corona virus vaccine will be ready soon, achieving so will be challenging in reality. However, no study has been conducted on the awareness of the COVID-19 vaccine in Iraq. Therefore, there is a more prominent need to evaluate their knowledge and awareness among HCWs.